Biometric measurements of the nasal area of newborns for the development of a nasal protector model: cross-sectional study - Mércia Lisieux Vaz da Costa Mascarenhas; Bruna Luizy dos Santos Guedes; Marcella Martins Barbosa Ferreira; Magda Kelanny de Oliveira dos Santos; Regina Célia Sales Santos; Ingrid Martins Leite Lúcio
ABSTRACT Objective: To correlate the biometric measurements of the nasal area of premature and term newborns to provide parameters for a nasal protector model. Method: A crosssectional descriptive study, carried out in the neonatal joint accommodation, intermediate and intensive care units of a hospital in Maceio, Alagoas, with a total of 300 newborns, divided into two groups: 150 term and 150 premature. Neonatal history data and 1200 digital photographs were used for biometric measurements. Results: The groups were homogeneous regarding gender, weight and length of the newborn. The measurements of nasal width, distance from the wing of the nose to the right and left columella midline, right and left nasal introitus area, length of the right and left nasal dorsum were different when compared in groups according to gestational age and weight ranges - very low weight, low weight and appropriate weight for gestational age (p<0.05). Conclusion: The data obtained provide parameters for creating a nasal protector for newborns using prongs, considering anatomical aspects.